Design Considerations for the Next Generation Hip Resurfacing Implant: Commentary. Issue 1 (February 2017) - Su, Edwin P.
The current generation of hip resurfacing consists of a metal-on-metal ball and monoblock socket of minimal thickness. Although results in certain patient subgroups have been excellent at up to 15 years of follow-up, other subgroups have had poor results. The hard-on-hard bearing is susceptible to edge-loading conditions and may produce excessive metallic debris; furthermore, other patients have had allergic reactions to the metal byproducts. In both situations, there can be clinical failures from adverse local tissue reactions. As such, the role of hip resurfacing has diminished over the last decade because of these issues. Developing the next generation hip resurfacing is essential to address these problems, and there are multiple design considerations in doing so. The choice of materials will be of prime concern, with the decision to use a hard-on-soft or hard-on-hard articulation. The dimensions of the resurfacing implant also pose a challenge, because of the requirement to preserve the bone. Fixation of the implant is another area of interest, in order to maximize implant longevity.